Effectiveness of Patient Health Services at IPKT RSUD.: Efektivitas Pelayanan Kesehatan Pasien di IPKT RSUD. - Kartikasari, Trisnaning; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2024)
The study "Quality of Patient Health Services at the Integrated Cancer Service Installation" conducted at a district general hospital aimed to assess the health service quality for cancer patients. The researchers used a descriptive qualitative method, including observation and interviews, and employed the theory of effectiveness by Parasuraman, Zeithami, and Berry (1988) with indicators such as tangibles, reliability, responsiveness, assurance, and empathy. The results indicated a need to increase facilities, good performance by the officers, and positive findings in terms of responsiveness, assurance (5S implementation), and empathy. The implication of the study is to highlight areas for improvement in health service quality for cancer patients. The title for the scientific article could be "Enhancing Cancer Patient Care: A Quality Assessment of Health Services." Highlight : The field of quality assessment in cancer care is relatively new, and investigators are just beginning to identify meaningful indicators of quality for many aspects Cancer centers must assist their patients and families to comprehend the overall prognosis, benefits of treatments, and possible harms fully The ability to distinguish high-quality from low-quality care across oncology practices remains a challenge Keywords: cancer, health service quality, assessment, improvement, patients.